Predictive Model of Risks in Railroad Transport when Diagnosing Axle Boxes of Freight Wagons (preiew) - Muradian, Leontii A.; Pitsenko, Iryna; Shaposhnyk, Vladyslav Yu.; Shvets, Angela O.; Shvets, Anzhelika O. (SAGE Publishing, 2022)
ENG: The research is aimed at developing a predictive model of the risks in railroad transport when using diagnostics of the axle boxes of freight wagons, which will allow assessing traffic safety during the operation of freight wagons. To develop a predictive model of the risks in railroad transport, the approaches of the probability theory were used. The constructed predictive model of the risks makes it possible to assess traffic safety during freight transportations; to determine further measures to reduce them; to evaluate the diagnostic method. The authors developed a predictive model of the risks in railroad transport when using the diagnostic methods of freight wagons’ axle boxes during maintenance and repair of axle box. This model includes the probability of failure-free operation of the axle boxes of freight wagons, the probability of identifying of the technical condition of the axle boxes of freight wagons, the significance of the diagnostic parameter and its relative assessment after appropriate maintenance, repair or technical control.

UKR: Дослідження спрямоване на розробку моделі прогнозування оцінки ризиків на рухомому складі залізниць під час діагностування вагонних буксів, що дозволить оцінити безпеку руху поїздів. Для розробки моделі прогнозування оцінки ризиків на рухомому складі використано методи теорії ймовірностей. Представлена модель прогнозування дозволяє: оцінити безпеку руху під час здійснення вантажних перевезень, визначити подальші заходи відносно зниження ризиків; встановити ефективність методів діагностики. Авторами цієї роботи розроблено модель прогнозування оцінки ризиків при технічному обслуговуванні та ремонті рухомого складу з використанням методів діагностики вагонних букс. Модель прогнозування включає можливість безвідмовної роботи вагонних букс рухомого складу для вантажних перевезень, значимість діагностичного параметра та його відносну оцінку після відповідного технічного обслуговування, ремонту або технічного контролю буксового вузла.

RUS: Исследование направлено на разработку модели прогнозирования оценки рисков на подвижном составе железнодорожных дорог во время диагностирования вагонных букс, которое позволит оценить безопасность движения поездов. Для разработки модели прогнозирования оценки рисков на подвижном составе использованы методы теории вероятностей. Представленная модель прогнозирования позволяет: оценить безопасность движения при осуществлении грузовых перевозок, определить дальнейшие мероприятия по снижению рисков; установить эффективность методов диагностики. Авторами этой работы разработана модель прогнозирования оценки рисков при техническом обслуживании и ремонта подвижном составе с использованием методов диагностики вагонных букс. Модель прогнозирования включает вероятность безотказной работы вагонных букс подвижного состава для грузовых перевозок, значимость диагностического параметра и его относительную оценку после соответствующего технического обслуживания, ремонта или технического контроля буксового узла.
Модель прогнозування ризиків на залізничному транспорті під час діагностики букс вантажних вагонів
Модель прогнозирования рисков на железнодорожном транспорте при диагностике букс грузовых вагонов
L. Muradian: ORCID 0000-0003-1781-4580, І. Pitsenko: ORCID 0000-0002-5674-0337, V.Shaposhnyk: ORCID 0000-0003-4701-6491, Angela Shvets:ORCID 0000-0002-8469-3902, Anzhelika Shvets: ORCID 0000-0002-0717-2521
Keywords: automatic railroad traffic safety; risks; axle box; diagnostics; freight wagons; railroad transport; безпека руху поїздів; ризики; букси; діагностика; вантажні перевезення; вагони; рухомий склад; безопасность движения поездов; риски; буксы; диагностика; грузовые перевозки; вагоны; подвижной состав; КТБМ; КВВГ